2011
DOI: 10.1007/s12012-011-9114-2
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Effects of Hesperetin against Doxorubicin-Induced Oxidative Stress and DNA Damage in Rat

Abstract: Doxorubicin is a widely used chemotherapeutic agent; however, its clinical uses are limited due to its cardiotoxicity associated with an induction of oxidative stress. This study was aimed to investigate the protective effect of hesperetin against doxorubicin-induced cardiotoxicity in rats. Doxorubicin was administered at the dosage of 4 mg/kg bw/week, ip for a period of 5 consecutive weeks. Hesperetin was administered at the dosages of 25, 50 and 100 mg/kg bw, po by gavage for 5 consecutive days in a week for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(52 citation statements)
references
References 47 publications
2
49
0
1
Order By: Relevance
“…injection of DOX (15 mg/kg) on the 8 th day. This DOX dose was selected as it has been used previously to induce acute cardiotoxicity in male albino rats [18]; [19]. Doses of MO were selected based on previously reported pharmacological properties of this plant [20].…”
Section: Methodsmentioning
confidence: 99%
“…injection of DOX (15 mg/kg) on the 8 th day. This DOX dose was selected as it has been used previously to induce acute cardiotoxicity in male albino rats [18]; [19]. Doses of MO were selected based on previously reported pharmacological properties of this plant [20].…”
Section: Methodsmentioning
confidence: 99%
“…Rat, treated with DOX and hesperetin (50 and 100 mg/kg b.w., p.o. by gavage for 5 consecutive days in a week), showed decreased ROS production and cells apoptosis [178]. Hesperetin (30 mg/kg, p.o.)…”
Section: In Vivo Effects Of Polyphenols Against Oxidative Stress-imentioning
confidence: 99%
“…In addition to oxidative parameters, hesperetin significantly decreased DOX-induced heart apoptosis as confirmed by the results of halo and terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assays. Comet assay findings have also shown that DNA damage is attenuated following hesperetin treatment (49). It seems that like other flavonoids, hesperidin interferes with the cellular apoptotic cascade to protect cardiomyocytes from DOX injury.…”
Section: Hesperidin (5)mentioning
confidence: 95%